Design of high entropy alloys: A single-parameter thermodynamic rule. (15th July 2015) - Ye, Y.F.; Wang, Q.; Lu, J.; Liu, C.T.; Yang, Y.
Abstract : Assuming random mixing of atoms, design of high entropy alloys (HEAs) was used to follow a simple route by maximizing their configurational entropy of mixing. Here we propose a single-parameter design paradigm taking into account formation enthalpy and the excessive entropy of mixing, which arises from dense atomic packing and atomic size misfit. The proposed paradigm is verified using the data hitherto reported and proven to be a physically accepted thermodynamic parameter for the design of HEAs.